The analysis of Calsium (Ca), Magnesium (Mg), Sodium (Na) and Posphorus (P) ijn Beluntas (Pluchea indica L.) Leaves - Fitriani, Eva; Walanda, Daud K.; Hamzah, Baharuddin (Jurnal Akademika Kimia, 2019)
Beluntas are bushes that may consumed as vegetable which mostly founded in Central of Sulawesi. The research purposes to determine the concentration of calcium (Ca), magnesium (Mg), sodium (Na), and posphorus (P) in beluntas leaves (pluchea indica L.). The concentration of Ca, Mg, and Na were obtained using atomic absorption spectrophotometer and the concentration of P was obtained using spectrodirect spectrophotometer. The average concentration of mineral in beluntas leaves are Ca 678.71 mg/100g, Mg 93.38 mg/100g, Na 198.11 mg/100g, and P 29.84 mg/100g.